Unintended consequences of human actions - Ermolaeva, E. P. (Elena Pavlovna) (University Press of America, 2011)
"Using a mixed-method approach, Untended Consequences of Human Actions documents a wide range of unintended and unanticipated consequences of human actions. The major message is the urgent need to review a range of possible outcomes of human actions. During these fragile times "looking down the road" has become imperative."--Page 4 of cover.